Response analysis and damage mitigation of buried continuous pipes subjected to faulting actions - Perdibuka, Dardan. (Thesis (Ph.D.)-Bogazici University.Kandilli Observatory and Earthquake Research Institute, 2022., 2022)
Buried continuous steel pipelines are critical lifelines failure of which under fault rupture incidents may lead to significant and deteriorating environmental and socio economic outcomes. Proper understanding and estimation of the mechanical behavior of buried steel pipes under such geohazards and investigation of means of mitigating these deleterious effects is of paramount importance. This thesis aimed at developing rigorous and simplified numerical models of the problem to realistically simulate the behavior of buried continuous pipes under strike-slip fault rupture-induced permeant ground deformations. The response of buried pipe cases under the fault load was investigated with respect to the variation of fault crossing angle (β) and pipe wall thickness (t). The second phase of this dissertation involved the investigation of the effect of four mitigation techniques to protect the buried pipe against fault rupture-induced damages. Lastly, a case study involving the evaluation of the effect of using CFRP wraps on the response of Thames Water Pipe which suffered great damage during the devastating 1999 Izmit is presented. The outcomes of this thesis indicate that the performance of the pipeline is sensitive to the variation of fault crossing angle and pipe wall thickness, increasing both parameters lead to overall improved pipe performance. Results indicate that all mitigation approaches offer certain degrees of improvement, where most effective mitigation approach is the wrapping of the pipeline surface with CFRP wraps while the use of controlled-low strength material was the least effective approach. Comparison of simplified and rigorous numerical models revealed that a good agreement exist between the approaches. Lastly, evaluation of the response of Thames Water Pipe protected using CFRP indicates that despite the considerable reduction in stresses and strains complete avoidance of failure for this particular case does not seem to be attainable.
Keywords: Faults (Geology); Steel pipe -- Design and construction -- Standards.; Pipelines -- Design and construction.; Pipelines -- Safety measures.; İzmit Earthquake, Turkey, 1999.